Listening to farmers - Masianini, Bernadette; Rokotuibau, Mereani (Technical Centre for Agricultural and Rural Cooperation, 2009)
Extension officers in the Pacific are working with farmers to produce DVDs, printed guides and radio and TV programmes in order strengthen rural economies